Peran Pendidikan Agama Islam Dalam Membangun Pemahaman Iddah Bagi Perempuan Yang Hamil Pra Nikah: Studi Kasus Di Kecamatan Ngawi Jawa Timur - Rafiqa Nora Elfiana; Zaenal Abidin (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
This study aims to analyze the role of Islamic Religious Education (PAI) in shaping the understanding of iddah among women experiencing premarital pregnancy in Ngawi District, East Java. This research employs a qualitative field research design with a phenomenological approach. Data were collected through in-depth interviews, observations, and documentation. The findings indicate that PAI plays a significant role in improving the understanding of iddah; however, its implementation is not yet optimal due to low public awareness and strong socio-cultural influences. Persuasive and empathetic approaches are found to be more effective in helping women understand and practice the obligation of iddah